(untitled) - David Nunan (Oxford, 1999)
The book contains three sections. Section 1: Explanation, outlines the theoretical background to the topic in question. Section 2: Demonstration, discusses the relationship between theory and practice. Sec 3: Exploration, suggests small-scale research activities teachers can carry out in the process of their own teaching.
Keywords: language and languages - study and teaching